KOLONI SEMUT Myopopone castanea SMITH (hymenoptera : formicidae) SEBAGAI PREDATOR Oryctes Rhinoceros L. (coleoptera: scarabaidae) PADA ONGGOKAN BATANG SAWIT DI LABORATORIUM - rini susanti (Program Studi Agroteknologi Fakultas Pertanian, 2017)
Oryctes rhinoceros (Coleoptera: Scarabaeidae) is an important pest in palm oil plants in Indonesia. Biological control is one of the pest control methods O. rhinoceros L. Natural enemies representing the world of insects can be classified into two predators and parasitoids. Ants M. Castanea as a predator on pest Oryctes rhinoceros can be bred in bulk. Breeding mass necessary BioEkologi understanding of natural enemies. The purpose of this study was to determine the ants of colony Mypoponae castanea as predators of the palm stem borer O. rhinoceros (Coleoptera: Scarabaidae) on a pile of oil palm trunk in laboratory.This research was conducted at the Laboratory of Pest Plant of the Faculty of Agriculture, University of Sumatra Utara, Medan (Â± 25 m above sea level). This research was conducted in November 2014 to Agustus 2015. The results showed a colony of M. castanea had one queen with 5-6 male ants and 60-70 worker ants in the laboratory.